NavBelt and the Guide-Cane [obstacle-avoidance systems for the blind and visually impaired]. - Shoval, S. (IEEE Robotics and automation magazine)
NavBelt and GuideCane are computerized devices based on advanced mobile robotics obstacle-avoidance technologies. NavBelt is worn by the user like a belt and is equipped with an array of ultrasonic sensors. It provides acoustic signals via a set of stereo earphones that guides the user around obstacles or "displays" a virtual acoustic panoramic image of the traveler's surroundings. One limitation of the NavBelt is that it is exceedingly difficult for the user to comprehend the guidance signals in time to allow fast walking. A newer device, called GuideCane, effectively overcomes this problem. The GuideCane uses the same mobile robotics technology as the NavBelt but is a wheeled device pushed ahead of the user via an attached cane. When the GuideCane detects an obstacle, it steers around it. The user immediately feels this steering action and can follow the GuideCane's new path easily without any conscious effort. This article describes the two devices, including the mechanical, electronic, and software components, user-machine interface, and some experimental results.